Microentrepreneurship in Developing Countries - Seema Jayachandran (Institute of Labor Economics (IZA), 2020)
This article reviews the recent literature in economics on small-scale entrepreneurship ("microentrepreneurship") in low-income countries. Major themes in the literature include the determinants and consequences of joining the formal sector; the impacts of access to credit and other financial services; the impacts of business training; barriers to hiring; and the distinction between self-employment by necessity and self-employment as a calling. The article devotes special attention to unique issues that arise with female entrepreneurship.
Keywords: L26; J16; J24; 330; small businesses; female entrepreneurship; self-employment; informal sector